2015
DOI: 10.1051/0004-6361/201526228
|View full text |Cite
|
Sign up to set email alerts
|

Forecasts for the detection of the magnetised cosmic web from cosmological simulations

Abstract: The cosmic web contains a large part of the total gas mass in the Universe, but it is difficult to detect at most wavelengths. Synchrotron emission from shock-accelerated electrons may offer the chance of imaging the cosmic web at radio wavelengths. In this work we use 3D cosmological ENZO-magnetohydrodynamic simulations (combined with a post-processing renormalisation of the magnetic field to bracket for missing physical ingredients and resolution effects) to produce models of the radio emission from the cosm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(150 citation statements)
references
References 93 publications
6
144
0
Order By: Relevance
“…A subset of our simulations also made use of the recent porting of the Dedner algorithm onto CUDA (Li et al 2010), which runs ∼ 4 times faster on Graphics Processing Units (GPU), compared to the performance on CPUs. This suite of runs belongs to a larger suite of MHD cosmological simulations ("CHRONOS++"), designed to investigate the origin of extragalactic magnetic fields (Vazza et al 2014(Vazza et al , 2015.…”
Section: Magnetic Field Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…A subset of our simulations also made use of the recent porting of the Dedner algorithm onto CUDA (Li et al 2010), which runs ∼ 4 times faster on Graphics Processing Units (GPU), compared to the performance on CPUs. This suite of runs belongs to a larger suite of MHD cosmological simulations ("CHRONOS++"), designed to investigate the origin of extragalactic magnetic fields (Vazza et al 2014(Vazza et al , 2015.…”
Section: Magnetic Field Modellingmentioning
confidence: 99%
“…This is expected, because efficient dynamo amplification within structures can develop only if the gas flow is turbulent enough, which requires much larger resolution (e. g. Cho et al 2009;Beresnyak & Miniati 2016). To overcome the limitations of resolution, similar to Vazza et al (2015), we renormalized the field strength of each cell in post-processing so that the magnetic field energy is 1% of the Vazza et al 2014). In order to bracket the uncertainties of where the small-scale dynamo process starts operating, we produced two versions of this run, by renormalising the magnetic energy wherever the gas density is ρcr,g (where ρcr,g is the critical gas density) or only limited to where the gas density is 50ρcr,g.…”
Section: Magnetic Field Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Simulations including magnetic field evolution along with the structure formation and radiative cooling can provide predictions for the radio emission from the large scale structure based on the recipes for production of relativistic electrons (Hoeft & Brüggen, 2007;Donnert et al, 2013;Vazza & Brüggen, 2014;Vazza et al, 2015b). It has been shown that a saturation of magnetisation can be achieved in a fully turbulent medium and there is near equipartition between the magnetic field and kinetic energy densities (e. g. Subramanian, Shukurov & Haugen, 2006;Iapichino & Brüggen, 2012).…”
Section: Simulationsmentioning
confidence: 99%
“…A radio detection of filaments has been predicted in regions where magnetic field is about ∼10 -100 nG (Vazza et al, 2015a). Recent MHD simulations using EN ZO have predicted that a non-detection with the SKA can place constraints on the magnetic energy in the WHIM to be less than ∼ 1% of the thermal energy (Vazza et al, 2015b).…”
Section: Superclusters and Filamentsmentioning
confidence: 99%